Treatment of Posttraumatic Stress Disorder: A State-of-the-art Review - Burback, Lisa; Brult-Phillips, Suzette; Nijdam, Mirjam J.; McFarlane, Alexander; Vermetten, Eric (Current Neuropharmacology, 2024)
This narrative state-of-the-art review paper describes the progress in the understanding and treatment of Posttraumatic Stress Disorder (PTSD). Over the last four decades, the scientific landscape has matured, with many interdisciplinary contributions to understanding its diagnosis, etiology, and epidemiology. Advances in genetics, neurobiology, stress pathophysiology, and brain imaging have made it apparent that chronic PTSD is a systemic disorder with high allostatic load. The current state of PTSD treatment includes a wide variety of pharmacological and psychotherapeutic approaches, of which many are evidence-based. However, the myriad challenges inherent in the disorder, such as individual and systemic barriers to good treatment outcome, comorbidity, emotional dysregulation, suicidality, dissociation, substance use, and trauma-related guilt and shame, often render treatment response suboptimal. These challenges are discussed as drivers for emerging novel treatment approaches, including early interventions in the Golden Hours, pharmacological and psychotherapeutic interventions, medication augmentation interventions, the use of psychedelics, as well as interventions targeting the brain and nervous system. All of this aims to improve symptom relief and clinical outcomes. Finally, a phase orientation to treatment is recognized as a tool to strategize treatment of the disorder, and position interventions in step with the progression of the pathophysiology. Revisions to guidelines and systems of care will be needed to incorporate innovative treatments as evidence emerges and they become mainstream. This generation is well-positioned to address the devastating and often chronic disabling impact of traumatic stress events through holistic, cutting-edge clinical efforts and interdisciplinary research.
Keywords: psychedelic